BET-bromodomain inhibitors modulate epigenetic patterns at the diacylglycerol kinase alpha enhancer associated with radiation-induced fibrosis. Issue 1 (October 2017) - Valinciute, Gintvile; Weigel, Christoph; Veldwijk, Marlon R.; Oakes, Christopher C.; Herskind, Carsten; Wenz, Frederik; Plass, Christoph; Schmezer, Peter; Popanda, Odilia
Abstract: Background and purpose: Fibrosis is a frequent adverse effect of radiotherapy and no effective treatments are currently available to prevent or reverse fibrotic disease. We have previously identified altered epigenetic patterns at a gene enhancer of the diacylglycerol kinase alpha ( DGKA ) locus in normal skin fibroblasts derived from fibrosis patients. An open chromatin pattern related to radiation-inducibility of DGKA is associated with onset of radiation-induced fibrosis. Here, we explore epigenetic modulation of DGKA as a way to mitigate predisposition to fibrosis. Material and methods: We studied the effect of the BET-bromodomain inhibitors (JQ1, PFI-1) on DGKA inducibility in primary fibroblasts. Hence, DGKA transcription was additionally induced by the radiomimetic drug bleomycin, and DGKA mRNA expression, histone H3K27 acetylation and downstream markers of profibrotic fibroblast activation after BET-bromodomain inhibition were determined. Results: BET-bromodomain inhibition suppressed induction of DGKA in bleomycin-treated fibroblasts, reduced H3K27ac at the DGKA enhancer and repressed collagen marker gene expression. Alterations in fibroblast morphology and reduction of collagen deposition were observed. Conclusion: For the DGKA enhancer, we show that BET-bromodomain inhibitors can alter the epigenetic landscape of fibroblasts, thus counteracting profibrotic transcriptional events. Interference with epigenetic patterns of fibrosis predisposition may provide novel preventive therapies that improve radiotherapy.